2010
DOI: 10.1016/j.ridd.2009.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Low dimensional temporal organization of spontaneous eye blinks in adults with developmental disabilities and stereotyped movement disorder

Abstract: This study investigated the mean rate and time-dependent sequential organization of spontaneous eye blinks in adults with intellectual and developmental disability (IDD) and individuals from this group that were additionally categorized with stereotypic movement disorder (IDD+SMD). The mean blink rate was lower in the IDD+SMD group than the IDD group and both of these groups had a lower blink rate than a contrast group of healthy adults. In the IDD group the n to n+1 sequential organization over time of the ey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…To assess temporal organization, we examined the second order property of stereotyped responses, that is, the difference between consecutive inter-response intervals. Lee et al (2010) used the same approach to identify the temporal structure in spontaneous blinking using adjacent interblink intervals. This analysis showed decreased complexity of eye-blinking in individuals with intellectual disability versus controls.…”
Section: Methods and Data Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…To assess temporal organization, we examined the second order property of stereotyped responses, that is, the difference between consecutive inter-response intervals. Lee et al (2010) used the same approach to identify the temporal structure in spontaneous blinking using adjacent interblink intervals. This analysis showed decreased complexity of eye-blinking in individuals with intellectual disability versus controls.…”
Section: Methods and Data Analysismentioning
confidence: 99%
“…These investigators showed that intervals between tics were not random and that the temporal structure in the tic time series could be uncovered using several statistical approaches or models. In an intriguing set of studies, Newell et al have shown increased regularity in movements associated with upright postural stability (Bodfish, Parker, Lewis, Sprague, & Newell, 2001), sitting (Newell & Bodfish, 2007), and spontaneous blinking (Lee, Bodfish, Lewis, & Newell, 2010) in individuals with neurodevelopmental disorders who engaged in stereotyped behavior versus matched controls. Finally, as far as we are aware, there has been no attempt to address the intriguing question of whether such temporal characteristics interact with developmental trajectory.…”
Section: Introductionmentioning
confidence: 99%